PERBEDAAN UNSAFE ACTIONS ANTAR SHIFT KERJA PADA BAGIAN THREADING UNIT PRODUKSI I PT X DI SURABAYA - Jenius Setio Insanno (The Indonesian Journal of Occupational Safety and Health, 2016)
PT. X is one of the companies that produces iron pipe in Indonesia. Unit of production I PT. X threading part used work shift system. Few months ago there was an accident happened to a night shift workers threading part, and it caused them to be rushed to the hospital and got medical help. The purpose of this research was to analyze the difference between unsafe action on work shifts threading of PT. X. This research was an observational descriptive study that used crossectional approach. The population of this research was all workers shift threading part of PT. X which were consisted of 30 people. Determination of the sample was using total population method that involved 30 people. This research used primary data based on the results of observation, interview and secondary data from the company. The results showed that the highest frequency of low unsafe action was at morning shift wich was 96,7%. But it got decreased until 90% at evening shift, and got decreased even more until 60% at night shift. The difference of unsafe action can be caused by lack of supervision about safety at evening shift and night shift, and it can be caused by disturbed circadian rhytm of the workers’ bodies. The company should increase the coordination about unsafe action supervision between HSE and related supervisor. Advice to workers, especially night shift workers, are optimizing the leisure time while waiting the materials and use it for getting some rest to keep their body away from fatigue conditions.Keywords: unsafe action, work shift